Legal Analysis of The Problem of The Imposition of Interest Rate On Online Loans - Tata PELITA; Sihabudin SIHABUDIN; Djumikasih DJUMIKASIH (International Journal of Environmental, Sustainability, and Social Science, 2021)
The development of the digital economy has provided various services that make it easier for the community, one of which is the presence of information technology-based lending and borrowing services or online loans through Fintech. However, the issue of online lending or financial technology peer to peer lending (P2P fintech) is increasingly in the public spotlight. The most recent case of a Kindergarten teacher in Malang entangled in a loan of Rp. 40 million in 24 online loan service providers due to continuous default. This paper will examine the problems with online loans from the point of view of interest rates in this case related to the credit agreement and how or suggestions to overcome these problems. The research method used in this research is normative juridical research using a statutory approach and a case approach. The results of this study indicate that the problem of imposing interest rates on online loans occurs because Article 17 Paragraph (1) of POJK Number 77 of 2016 creates uncertainty in the practice of determining interest rates and arrangements regarding limits on the imposition of interest rates are only regulated through the association's code of ethics.